IMPLEMENTATION OF THE PROJECT BASED LEARNING MODEL ASSISTED WITH SOCIAL MEDIA MARKETING TO IMPROVE STUDENT LEARNING OUTCOMES IN CREATIVE PRODUCT AND ENTREPRENEURSHIP SUBJECTS - Winarsih, Tri; Anas, M.; Forijati, Forijati (Nusantara Economics and Entrepreneurships Journals, 2024)
The aim of this research is 1) to describe how to improve student learning outcomes through the Project Based Learning learning model assisted by Social Media Marketing in Creative Products and Entrepreneurship subjects in class XIIOTKP3 SMK Negeri 2 Blitar, 2) to describe the results of implementing the Project Based Learning learning model assisted with Social Media Marketing in the Creative Products and Entrepreneurship subjects in class XIIOTKP3 at SMK Negeri 2 Blitar. 3) To describe whether the Project Based Learning learning model assisted by Social Media Marketing in the subjects of Creative Products and Entrepreneurship can improve the learning outcomes of class XIIOTKP3 students at SMK Negeri 2 Blitar. This type of research is Classroom Action Research (PTK) or Classroom Action Research because the researcher is directly involved in the research process from the beginning to the end of the research. The results of this research show that students' cognitive aspect learning outcomes increased by 56%. This was proven in the first cycle of students who got a minimum score of 70 as many as 16 people or 44%, while in cycle II who got a minimum score of 70 as many as 36 people or 100% were declared complete. The affective aspect of student learning activities increased by 39%. This was proven in the first cycle of students who were declared complete 22 or 61%, while in cycle II those declared complete reached 36 people or 100%. Likewise, in the psychomotor aspect there was an increase of 53%. This was proven in cycle I, 17 students were declared complete or 47%, while in cycle II 36 students or 100% were declared complete. Based on the results of this research, it can be concluded that the application of the Project Based Learning learning model assisted by Social Media Marketing can improve the learning achievement of Class XIIOTKP3 students at SMK Negeri 2 Blitar, especially in the subjects of Creative Products and Entrepreneurship.